Algeria : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
In 1994-98, Algeria was successful in restoring macroeconomic stability and implementing structural reforms. The fiscal position deteriorated in the first part of 1999, owing to low oil prices. Executive Directors supported the reform program introduced in early 2000, and welcomed its emphasis on accelerating reform of the banking and public sector companies but stressed the need for detailed implementation plans. The economic environment should be improved to promote private economic activity, including domestic and foreign investment. The authorities are urged to accelerate trade liberalization.